ANALISIS TENTANG FAKTOR PENYEBAB MASYARAKAT MEMILIH JOKO WIDODO-JUSUF KALLA PADA PEMILIHAN PRESIDEN TAHUN 2014 DI KECAMATAN MERAL KABUPATEN KARIMUN - Dwi Putri Ayunani Bahri; Gimin '; Sri Erlinda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Absract : This research have background by the victory of Joko Widodo-Jusuf Kalla in the president general election on 2014 at the Meral Sub-district, Karimun Regency, there where on the six political districts in the Meral Sub-district, Karimun Regency was won about Jokowi-Jusuf Kalla with 10.932 votes (64,17%), formulation of the problem in this research is what are the factors of society elect Joko Widodo-Jusuf Kalla in the president general election on 2014 at the Meral Sub-district, Karimun Regency, the purpose of this research is to know the infect factors of the society elect Joko Widodo-Jusuf Kalla in the president general election on 2014 at the Meral Sub-district, Karimun Regency, there was 120 respondents as the samples with the random selesction, 20 respondents taken in the each political district, the sampling technique on this research are use purposive sampling method, data collection instruments are quitionnaire and interview. Result about the anlysis of infect factors of the society elect Joko Widodo-Jusuf Kalla in the president general election on 2014 at the Meral Sub-district, Karimun Regency are personality and human relationship factor that was owned by this two figures with 15,78% percentage, then followed by knowledgement factor with 15,58% percentage, psychology factor with 14,17% percentage, religion factor with 13,6% percentage, leadership factor with 12,13% percentage, communication skill with 10,08% percentage, ethnic and regional cultural factors with 10% percentage, and the last is family factor with 8,5%.Keywords : infect factor, society, electof Joko Widodo-Jusuf Kalla